INVESTIGATING THE EFFECT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND ORGANIZATIONAL PRODUCTIVITY ON KNOWLEDGE MANAGEMENT OF EMPLOYEES OF SPORTS AND YOUTH DEPARTMENTS OF EAST AZERBAIJAN PROVINCE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is conducted to investigate the effect of organizational citizenship behavior and organizational productivity on knowledge management of employees of sports and youth departments of East Azerbaijan province. According to the data collection, this research is a field research method. Among the research methods, it is a descriptive correlational type and in terms of purpose, it is also practical. All employees of the sports and youth departments of East Azerbaijan province are the statistical population of this study. They are 320 people, 260 of whom work as office staff and 60 as contract workers according to the statistics inquired from the General Directorate of Sports and Youth of the province. Through Morgan and Krejcie's table, 176 people were determined as the sample size, and the sampling method was simple random. To analyze the data, first, the normality of the data was examined through the Kolmogorov-Smirnov test, and Smart PLS software was used to determine the effect between the variables. Convergent validity was calculated by AVE and the reliability of variables was calculated by Cronbach's alpha and combined reliability method (CR). SPSS software version 25 and Smart PLS were used for data analysis. Organizational citizenship behavior has a positive and significant effect on the knowledge management of employees of sports and youth departments of East Azerbaijan province according to the results. The results also showed that organizational productivity has a positive and significant effect on the knowledge management of employees of sports and youth departments of East Azerbaijan province.